2015
DOI: 10.1093/jxb/eru494
|View full text |Cite
|
Sign up to set email alerts
|

In the Solanaceae, a hierarchy of bHLHs confer distinct target specificity to the anthocyanin regulatory complex

Abstract: SummaryAnthocyanin biosynthesis is regulated by a transcription factor complex. Here, it is determined that the potential bHLH partners in this complex function in a hierarchy to control each other and the anthocyanin biosynthesis pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(143 citation statements)
references
References 41 publications
(73 reference statements)
10
120
1
2
Order By: Relevance
“…Therefore, despite the HF2 induction by VvWRKY26, petals of the fully complemented 35S:VvWRKY26 petunia plants have a reddish color typical of the cyanidin-based anthocyanin profile of the R27 background. The microarray analysis of petunia petals expressing VvWRKY26 also revealed the weak induction of a bHLH regulator of the flavonoid pathway, JAF13 , whose precise role in the pigmentation of petunia corollas still has to be fully elucidated (Quattrocchio et al, 1998; Montefiori et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the HF2 induction by VvWRKY26, petals of the fully complemented 35S:VvWRKY26 petunia plants have a reddish color typical of the cyanidin-based anthocyanin profile of the R27 background. The microarray analysis of petunia petals expressing VvWRKY26 also revealed the weak induction of a bHLH regulator of the flavonoid pathway, JAF13 , whose precise role in the pigmentation of petunia corollas still has to be fully elucidated (Quattrocchio et al, 1998; Montefiori et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In some species, such as Antirrhinum (Schwinn et al 2006), bHLHs of different clades appear to be interchangeable, while in others, e.g. the Solanaceae, it has been shown that AN1 is specifically required for activation of the anthocyanin biosynthetic pathway, while JAF13 regulates the anthocyanin pathway indirectly by regulating AN1 expression (Montefiori et al 2015). In kiwifruit, bHLH42 (belonging to clade B, AN1-like) appears to be slightly up-regulated during anthocyanin biosynthesis .…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…), PpMYBPA1 and PpMYB7 in peach (Ravaglia et al ., ; Zhou et al ., ) and MdMYB9 and MdMYB11 in apple (Gesell et al ., ; An et al ., ). Flavonoid‐related bHLH TFs can be divided into two clades, A and B (Montefiori et al ., ). Clade A includes GL3/EGL3 in Arabidopsi s, JAF13 in petunia and R in maize, whereas clade B consists of AN1 in petunia, TT8 in Arabidopsis and IN1 in maize.…”
Section: Introductionmentioning
confidence: 97%